Media and Political Transformations in Iraq after 2003 - mohe , ahmed qhalb; mohammed, mohammed jamel (The International and Political Journal, 2025)
Media represents a fundamental pillar in the construction of modern societies, playing a key role in knowledge dissemination, value formation, and the facilitation of social communication. With the rise of digital technologies and the emergence of the internet as an open platform, the media landscape has undergone profound transformations. Control over information is no longer exclusive to traditional institutions, as individuals now possess the tools for publishing and influence—ushering in a media environment characterized by plurality, speed, and direct interaction. In the Iraqi context, media prior to 2003 was under tight state control, functioning primarily as a propaganda tool aligned with the ruling regime and maintaining a unified national discourse. This centralization limited Iraq’s media presence on the international stage, especially in the face of dominant, often hostile, Western narratives. Following the fall of the regime in 2003, Iraq witnessed a chaotic media liberalization marked by the rapid proliferation of local and international satellite channels, and the influx of domestic and foreign actors. However, this expansion did not establish genuine media freedom, but rather exposed the weakness of professional media structures, deepened discourse fragmentation, and enabled the instrumentalization of media in sectarian and political conflicts—ultimately undermining state stability and coherence. This study aims to examine the role of Iraqi media after 2003 in shaping political awareness, analyzing its interaction with political and social developments, and assessing its influence on democratic transformation. Furthermore, it seeks to identify the challenges facing media in post-conflict environments—particularly politicization and foreign interference—while offering practical recommendations for building a professional, independent media capable of supporting democratic processes and fostering a culture of freedom and pluralism.